Toluidine blue stain and crystal violet stain versus H&E stain in the Diagnosis of Hirschsprung’s Disease: A Study in Sulaimani City in Kurdistan/Iraq - Yasseen, Hadeel Adnan (Annals of Pathology and Laboratory Medicine, 2015)
Background Hirschsprungâ€™s Disease (HD) is aÂ congenitalÂ disorder of theÂ colonÂ in which certain nerve cells, known asÂ ganglion cells are absent. Setting and Design: To demonstrate the efficacy of Cresyl Violet and Toluidine blue (Tb) special stains in the identification of ganglion cells in suspected Hirschsprungâ€™s disease and to find other adjuvant histological criteria for the diagnosis. Â Method: In Sulaimani Teaching Hospital and Pediatric teaching hospital in Sulaimani Governorate/ Kurdistan-Iraq a total of fifty non selected cases biopsied for suspected HD were stained with hematoxylin and eosin (H&E) stain and divided into two groups: HD and-non-HD. All cases then should be stained with Tb special stain to identify ganglion cells and to count mast cells in the submucosa. Cases were stained with Cresyl Violet special stain to identify ganglion cells. H&E- and Tb-stained sections were examined for the presence or absence of hypertrophic nerve fibers in the submucosa. Results: Both Cresyl violet and Tb stains were superior to H&E in the identification of ganglion cells with no statistically significant difference between the two stains. Mast cell count in the submucosa has no important effect on diagnosis while nerve bundle hypertrophy was found to be associated with absence of ganglion cells in Hirschsprung disease. Conclusions: Toluidine blue and/or Cresyl violet stains should to be used as the routine stain to highlight ganglion cells in suspected Hirschsprungâ€™s disease cases. Submucosal nerve bundle hypertrophy has to be assessed as an adjuvant histolological criterion.Â Â